2013
DOI: 10.1002/etc.2345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and copper pollution on soil community—extreme temperature events can lead to community extinction

Abstract: Global warming affects ecosystems and species' diversity. The physiology of individual species is highly influenced by changes in temperature. The effects on species communities are less studied; they are virtually unknown when combining effects of pollution and temperature. To assess the effects of temperature and pollution in the soil community, a 2-factorial soil mesocosms multispecies experiment was performed. Three exposure periods (28 d, 61 d, and 84 d) and 4 temperatures (19 °C, 23 °C, 26 °C, and 29 °C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 55 publications
3
18
0
Order By: Relevance
“…Since this study is part of a broader multi-species experiment (Menezes-Oliveira et al, 2013, 2014, hence a series of pre-treatments were required due to standardised purposes (e.g. drying to eliminate soil fauna).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since this study is part of a broader multi-species experiment (Menezes-Oliveira et al, 2013, 2014, hence a series of pre-treatments were required due to standardised purposes (e.g. drying to eliminate soil fauna).…”
Section: Discussionmentioning
confidence: 99%
“…The total Cu concentrations used at the two sites were different, which was in part to mimic equivalent effect concentrations taking the soil type differences into account (see Menezes-Oliveira et al 2013) as confirmed by the similar toxicity to invertebrates between soils using a factor of 10 as a consequence of variations in the bioavailability of Cu between soils. There is no analytical chemical method to confirm the bioavailable fraction as this of course also depends on the species trait and will be species specific.…”
Section: Soil Samples Richness (No Of Bands) Shannon Diversity (H) Ementioning
confidence: 99%
See 1 more Smart Citation
“…It has been given considerable focus and has currently an extensive suite of tools available for hazard assessment, far beyond the standard ecotoxicity test battery of many other species. The tools cover bioaccumulation (Amorim et al, 2011), avoidance (Bicho et al, 2015a), full life cycle test (Bicho et al, 2015b(Bicho et al, , 2016(Bicho et al, , 2017aSantos et al, 2017), embryotoxicity (Gonçalves et al, 2015), full life span (Gonçalves et al, 2017), multigenerational (Bicho et al, 2017b), multispecies (mesocosm) system (SMS) (Menezes-Oliveira et al, 2013), full transcriptome and microarray tool (Castro-Ferreira et al, 2014;Gomes et al, 2017), oxidative stress biomarkers (Ribeiro et al, 2015), energy metabolism and cellular energy allocation , genotoxicity via the comet assay (Maria et al, 2017), and metabolomics and proteomics. This species has further potential as it can be exposed via water for a short period and hence allows the assessment of other routes of exposure (Gomes et al, 2015b).…”
Section: Enchytraeid Toxicity Studies: Enchytraeus Crypticus/enchytramentioning
confidence: 99%
“…Global environmental change is leading to unprecedented levels of biodiversity loss ( Rockstrom et al , 2009 ). Anthropogenic drivers of decline, including habitat alteration ( Kerr and Deguise, 2004 ; Gallant et al , 2007 ), climate change ( Pearson and Dawson, 2005 ; Monahan and Hijmans, 2008 ) and pollution ( Menezes-Oliveira et al , 2013 ), perturb the physiological optimization of organisms ( Carey, 2005 ; Pörtner and Farrell, 2008 ). When unchecked, effects of species decline can cascade through ecosystems and trophic communities ( Duffy, 2003 ), leading to loss of specialist species ( White and Kerr, 2007 ) or even changes in system state ( Beisner et al , 2003 ).…”
Section: Introductionmentioning
confidence: 99%